EXPLORING THE RELATIONSHIP BETWEEN LACTIC ACID LEVELS AND CLINICAL OUTCOMES OF SEPSIS PATIENTS IN INTENSIVE CARE UNITS: IMPLICATIONS FOR NURSING PRACTICE - Rismawan Adi Yunanto; Wahyu Novia Fajriati; Ruris Haristiani (Nursing Sciences Journal, 2026)
Sepsis is a life-threatening condition frequently associated with clinical deterioration, including prolonged hospitalization and increased mortality risk. High lactate concentrations reflect tissue hypoxia and organ dysfunction, which may significantly worsen patient outcomes. However, previous studies on the association between lactate levels and clinical outcomes remain inconsistent. This study aimed to analyze the relationship between lactate levels, length of hospital stay, and mortality in sepsis patients in the intensive care unit. A retrospective observational cohort design was employed, with saturated sampling based on inclusion criteria (n=109). Data were collected from medical records with a total population of 134 patients. Results showed that the majority of sepsis patients were male, predominantly in the pre-elderly and elderly age groups. The most common comorbidities were pneumonia. Most patients had lactate levels >1.7 mmol/L, with prolonged hospitalization (≥3 days) observed and a mortality rate of 71.6%. Chi-square analysis revealed a significant association between lactate levels and both length of stay (p=0.039) and mortality (p=0.018). It can be concluded that elevated lactate levels were associated with prolonged hospitalization and increased mortality in sepsis patients. Lactate levels may serve as a prognostic marker, emphasizing the need for standardized sepsis management, including adherence to the “Hour-1 bundle” protocol, to improve patient outcomes.